2005
DOI: 10.1099/mic.0.27624-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Mycobacterium smegmatis unable to grow at acidic pH in the presence of the protonophore carbonyl cyanide m-chlorophenylhydrazone

Abstract: Mycobacterium smegmatis is able to grow and survive at acidic pH, and exhibits intracellular pH homeostasis under these conditions. In this study, the authors have identified low proton permeability of the cytoplasmic membrane, and high cytoplasmic buffering capacity, as determinants of intrinsic acid resistance of M. smegmatis. To identify genes encoding proteins involved in protecting cells from acid stress, a screening method was developed using the electrogenic protonophore carbonyl cyanide m-chlorophenylh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…The gene encoding 3-oxoacyl-[acylcarrier-protein] synthase was up-regulated 1.7-fold at pH 5.5 (fabH), and a fabH2 mutant was acid sensitive. In agreement with this observation, fatty acid metabolism was found to be an important component of the adaptation of Mycobacterium to growth at low pH (28,83).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The gene encoding 3-oxoacyl-[acylcarrier-protein] synthase was up-regulated 1.7-fold at pH 5.5 (fabH), and a fabH2 mutant was acid sensitive. In agreement with this observation, fatty acid metabolism was found to be an important component of the adaptation of Mycobacterium to growth at low pH (28,83).…”
Section: Discussionsupporting
confidence: 71%
“…In agreement with our observations, methionine biosynthesis appears to play a role in bacterial acid stress responses. In H. pylori, metB expression is activated at low pH by the ArsSR two-component system (67), and a metB-Tn mutant of Mycobacterium smegmatis was recovered in a screen designed to identify mutants unable to grow at low pH in the presence of a proton-motive force uncoupler (83). Finally, the main difference between an acid-resistant mutant of Bifidobacterium longum and its more sensitive parent is the overproduction of MetE, CysD, and MetB in the mutant (75).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies examining the physiology of mycobacteria at low pH indicate that the cell wall plays a critical role in resistance to acid. A large number of the few M. tuberculosis and M. smegmatis acid-sensitive mutants identified so far have defects in genes involved in cell wall functions (92,95,96), and many cell wall or lipid biosynthesis genes are transcriptionally regulated upon exposure to low pH (29,73,80). In addition, mycobacteria do not appear to display a classical acid tolerance response, in which prior exposure to mildly acidic conditions protects the bacteria in a more acidic environment.…”
Section: The Role Of the Cell Envelope In Acid Resistancementioning
confidence: 99%
“…Such strict coupling would imply that mycobacteria do not support uncoupled respiration: either they lack a conduit for proton reentry in the absence of the F 1 F o -ATP synthase or they are unable to adjust the proton permeability of the cytoplasmic membrane to allow a futile cycle of protons to operate. Recently, we have shown that the cytoplasmic membrane of M. smegmatis is extremely impermeable to protons (27).…”
mentioning
confidence: 99%